LINGKUNGAN KERJA FISIK, KOMITMEN DAN PELATIHAN TERHADAP KINERJA GURU DAN PEGAWAI DI SD SWASTA AL-AZHAR 1 MEDAN - Islamiati, Munica; Maya Putra, M. Umar; Muhajir, Ahmad (Fakultas Ekonomi Universitas Al-Azhar Medan, 2024)
This exploration recounts the tale of the connection between the actual workplace, responsibility and preparing at Al-Azhar 1 Medan Private Grade School. The factual strategy utilized is different relapse with a quantitative clear methodology utilizing traditional supposition tests first. The number of inhabitants in this review were educators and representatives at Al-Azhar 1 Medan Private Grade School, adding up to 37 respondents, determined from the quantity of laborers at Al-Azhar 1 Medan Private Primary School, so the absolute example in the review was 37 individuals. The consequences of this exploration show that to some extent the factors Actual Workplace (X1), Responsibility (X2) and Preparing (X3) meaningfully affect the Presentation of Educators and Representatives at Al-Azhar 1 Medan Private Grade School (Y), while at the same time the Climate is great Actual Work (X1), Responsibility (X2) and Preparing (X3) affect the Exhibition of Instructors and Representatives at Al-Azhar 1 Medan Private Primary School (Y).